DEVELOPMENT OF HEARING PERCEPTION IN SUBJECTS WITH COCHLEAR IMPLANT - Lazarovska, Vesna (Journal of Morphological Sciences, 2021)
Development of speech is a highly integrative process which has to incorporate harmonic functioning of many aspects such as anatomical, physiÐ¾logical, auditory, mental, emotional and social. Anatomical-physiological bases of hearing have been well studied. Cochlear implant is recommended in subjects who do not have any significant increase of the sound through the individual hearing amplifiers or have small benefit and also in subjects whose impairment is over 90dB to 500, 1000, 2000 and 4000 Hz.The aim of this study was to estimate the development of hearing perception in subjects with prelingual hearing impairment who used cochlear implant with regards to perception and identification of sounds from external environment. The results of the Test for development of hearing perception showed progression during the follow-up period at 6, 12 and 24 months. It was concluded that the longer the cochlear implant was used, the better results were achieved. Keywords: impaired hearing, cochlear implant, hearing perception, speech development https://doi.org/10.55302/JMS2141163l